Obtenção de biovitrocerâmicas por cristalização controlada do vitro 1Na2O.2CaO.3SiO2 - Guanabara Júnior, Paulo (Universidade Federal de São Carlos, 2003)
Glass-ceramics used as implant in tissue attachment bioactive classification type, show better mechanical strength than related glasses or ceramics, but without significant bioactivity loss. It was not analysed the bioactivity of a glass-ceramic from glasses with chemical composition 1Na2O. 2CaO. 3SiO2 (1N2C3S). This type of glass that does not possess phosphate in its composition, has its bioactive behavior known of literature in the glass phase and fully crystallized phase. With the objective to use such glass-ceramics as bioactive implant, the bioactivity was analysed in the range between glass 1N2C3S and the crystal. For this purpose sample of glass-ceramics were made with several crystallized fractions, by controlled crystallization, through thermal treatments in the range of 570oC to 700oC. These glass-ceramics were exposed to a solution that simulates the fluid of the body (SBF-K9) for several periods of time. The rate of hydroxycarbonateapatite (HCA) formation was determined using Fourier transform infrared spectroscopy (FTIR). The simultaneous mechanisms of performance were observed; a non-phosphat bioactive crystal phase 1N2C3S and the phosphorus ions in solid solution which are released from the structure promoting a HCA layer formation, already indicated in previous studies, of glass-ceramics compositions in vitro tests. All the glassceramics showed the formation of a well-developed HCA layer on its surface at less than 100 hours exposure time.
Bioglass-ceramics for controlled crystallization of the 1Na2O.2CaO.3SiO2 glass
Keywords: Material cerâmico; Vitrocerâmica; Hidroxicarbonatoapatia; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA